6x+4(-x+8)=4-3(x+5)

Simple and best practice solution for 6x+4(-x+8)=4-3(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+4(-x+8)=4-3(x+5) equation:


Simplifying
6x + 4(-1x + 8) = 4 + -3(x + 5)

Reorder the terms:
6x + 4(8 + -1x) = 4 + -3(x + 5)
6x + (8 * 4 + -1x * 4) = 4 + -3(x + 5)
6x + (32 + -4x) = 4 + -3(x + 5)

Reorder the terms:
32 + 6x + -4x = 4 + -3(x + 5)

Combine like terms: 6x + -4x = 2x
32 + 2x = 4 + -3(x + 5)

Reorder the terms:
32 + 2x = 4 + -3(5 + x)
32 + 2x = 4 + (5 * -3 + x * -3)
32 + 2x = 4 + (-15 + -3x)

Combine like terms: 4 + -15 = -11
32 + 2x = -11 + -3x

Solving
32 + 2x = -11 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
32 + 2x + 3x = -11 + -3x + 3x

Combine like terms: 2x + 3x = 5x
32 + 5x = -11 + -3x + 3x

Combine like terms: -3x + 3x = 0
32 + 5x = -11 + 0
32 + 5x = -11

Add '-32' to each side of the equation.
32 + -32 + 5x = -11 + -32

Combine like terms: 32 + -32 = 0
0 + 5x = -11 + -32
5x = -11 + -32

Combine like terms: -11 + -32 = -43
5x = -43

Divide each side by '5'.
x = -8.6

Simplifying
x = -8.6

See similar equations:

| x/5-8=7 | | -1/3x-4=12 | | 7.5(x-3)=-0.5x+25.5 | | -4/3x-3=-5/3-2x | | 125=5x^2 | | x/5-5=-9 | | 4a+a=40 | | -14m-10=32 | | -1/2c+3=-5/6 | | ((1/9)(2m-16))=((1/3)(2m+4)) | | -6d-9d+5d=60 | | -5/6-1/2 | | 6x+5=2x+5 | | 6(t-7)=9(t-4) | | 5x*x= | | 22/2/5 | | 1/2(5-2n)=n/2 | | 13t-3t=-60 | | -3(x-1)=-8x-12 | | 3t-3t=60 | | x^2/x+2-4/x+2 | | 2/5x-9=13 | | y=30/54 | | -8x-(3x-3x+6)=4-x | | 8=k+15 | | 3x^2+3y^2-15=0 | | (3n^2-2)(4n+1)=0 | | 17=y-1 | | 11x-7-10x=14 | | x^2+24x-480=0 | | 6x+x=-2 | | 22=6x-14 |

Equations solver categories